New method of surgical correction of lesser toes deformity - S. N. Leonova; I. V. Usoltsev; M. A. Kosareva (Acta Biomedica Scientifica, 2021)
Background. Patients’ dissatisfaction with the results of surgical correction of lesser toes deformities, the shortcomings of methods aimed at eliminating the lateral deviation of the toe in the metatarsophalangeal joint necessitated the development of a new surgical method.The aim. To evaluate short-term results of the new surgical method for the treatment of patients with lesser toes deformity, accompanied with deviation of the toe.Materials and methods. A method of surgical treatment of deviated deformity of the small toes is proposed. The method includes precise marking of the metatarsal osteotomy line according to the previously calculated parameters of optimal shortening and displacement of the metatarsal bone, performing oblique diaphyseal osteotomy of the metatarsal bone, displacing its distal part along the osteotomy plane. According to the proposed method, nine patients were operated on who had a syndrome of nonrigid hammer-like deformity of the second toe with lateral deviation of the toe in the metatarsophalangeal joint. In all patients, the deformity of the second toe was associated with hallux valgus.Results. As a result of the application of the proposed method, it was possible to achieve deformity correction, eliminate the lateral deviation of the second toe in the metatarsophalangeal joint, restore congruence in the joint, achieve consolidation of bone fragments without loss of correction, and improve the appearance and function of the foot. Three months after the operation, a statistically significant improvement was determined, according to the AOFAS LMIS scale, having reached 94.5 ± 4.64 points, which made it possible to speak about the achievement of a good functional result of treatment. Patients noted the opportunity to wear standard footwear, to carry out their labor activity, to engage in physical culture, were satisfied with the result.Conclusion. The use of the proposed new surgical method for deflected deformity of the lesser toes makes it possible to correct the deformity, eliminate lateral deviation of the toe, relieve pain syndrome, achieve a good cosmetic and functional result, restoring the patients’ ability to wear standard shoes.